Seni â€œSarafal Anamâ€ di Bengkulu: Makna, Fungsi dan Pelestarian - Muhammad Tarobin (Direktorat Jenderal Bimbingan Masyarakat Islam, 2015)
Abstract This article describes about the art of Sarafal anam in Bengkulu. This is important because the value of the history of the art. Transcription of the poem of Sarafal anam displayed in Bengkulu community tradition proves that the text of the Sarafal anam different from Sharf al-anam text is in Arabic tradition. Meanwhile, some of the poems indicating closeness between Syiâ€™ah and Sunni Islamic tradition. This article also describes three Sarafal anam meaning of art in Bengkulu society such as: togetherness, beauty, religiousity. The meaning of togetherness with tradition is still upheld in customary of Bengkulu, that is bimbang tradition. While the beauty of this art looks in appearance of the accompaniment of musical instruments like drum when it reached to the stage of a blow